Dalihan na tolu as a marketing strategy in attracting customer interest:Case study of PT Sipirok Nauli Medan branch - Muda, Indra; Barus, Rehia K. Isabella; Batubara, Beby Masitho; Suharyanto, Agung; Bukit, Niarita (Universitas Bunda Mulia, 2024)
This research aims to explore and gain a deeper understanding of the marketing strategies employed by PT. Sipirok Nauli Express in attracting customer interest. This research method used is descriptive qualitative, with data collection techniques involving in-depth interviews, observations, and documentation studies. The research informants consist of the Head of the PT Sipirok Nauli Express Medan Representative Office, ticketing staff, agents, warehouse staff, and 8 loyal customers of PT Sipirok Nauli Express Medan. Informants were selected using the snowball sampling technique. Based on the research findings, to increase the number of customers, the promotion strategy applied by the PT Sipirok Nauli Express Medan Representative Office focuses on three stages of marketing communication strategies. These strategies include the implementation of marketing communication objectives utilizing both conventional and digital promotional media; the implementation of segmentation and targeting through direct marketing strategies using local approaches such as local greetings (e.x., ipar, lae, oppung, bapak uda, amangoru, and anggi) to create familiarity, build familial and emotional relationships through regional approaches; and the implementation of differentiation and positioning. Amidst technological innovations and service improvements aimed at attracting customer interest, PT Sipirok Nauli Express adopts a unique approach by leveraging regional approaches to attract and retain customers.